2018
DOI: 10.1016/j.scitotenv.2018.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mercury contamination in viperine snakes, Natrix maura, in Western Europe

Abstract: The effects of Hg contamination are presumably widespread across the components of aquatic ecosystems, but investigations have been mainly focused on freshwater fish, because this biota represents a major source of Hg for human populations. Yet, the possible bioaccumulation of Hg on other freshwater meso- and apex-predators (e.g., amphibians, reptiles) has been largely overlooked, especially in Western Europe. In this study, the determinants of Hg concentrations were assessed for the viperine snake (Natrix mau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 58 publications
(57 reference statements)
1
18
0
Order By: Relevance
“…Alternatively, relatively high concentrations of both Hg and Zn could be linked to the composition of fish pellets used for fish farming that occur in many ponds of Brenne. Indeed, commercial fish pellets exhibit high Hg concentrations of marine origin (Hansson et al 2017; see also Lemaire et al 2018) and are enriched with Zn oxide (EFSA 2012). Future studies should usefully investigate both the origin of Hg and Zn as well as the physiological and toxicological consequences of elevated levels of these elements for E. orbicularis (Meyer et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, relatively high concentrations of both Hg and Zn could be linked to the composition of fish pellets used for fish farming that occur in many ponds of Brenne. Indeed, commercial fish pellets exhibit high Hg concentrations of marine origin (Hansson et al 2017; see also Lemaire et al 2018) and are enriched with Zn oxide (EFSA 2012). Future studies should usefully investigate both the origin of Hg and Zn as well as the physiological and toxicological consequences of elevated levels of these elements for E. orbicularis (Meyer et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…First, the management category of each pond does not seem to significantly influence Hg concentrations in turtles. This suggests that, in Brenne, intensive fish farming (in unprotected ponds) may not be responsible for the transfer of marine mercury through fish food as shown in trout farming systems (Hansson et al 2017;Lemaire et al 2018). Indeed, in our study area, fish farming is mainly dedicated to omnivorous species (i.e., carps) for which food supplementation is represented by corn, rather than commercial pellets based on proteins from fishery products of marine origin (Hansson et al 2017).…”
Section: Environmental Determinants Of Hg Concentrationsmentioning
confidence: 85%
“…Cryptic sources can further complicate our understanding of the extent of Hg contamination. For instance, it has recently been shown that fish farming is responsible for the transfer of marine Hg to areas that superficially appear unaffected from other sources of pollution (Hansson et al 2017; see also Lemaire et al 2018;Guillot et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations